Usefulness of anti-rabphilin-3A antibodies for diagnosing central diabetes insipidus in the third trimester of pregnancy - Sakurai, Kanako; Yamashita, Rika; Niituma, Satsuki; Iwama, Shintaro; Sugimura, Yoshihisa; Arihara, Zenei; Takahashi, Kazuhiro (ENDOCRINE JOURNAL, 2017)
[Abstract.] We report a 27-year-old pregnant woman with polyuria, polydipsia and headache in the third trimester of pregnancy. Hypernatremia (153 mEq/L), high plasma osmolality (300 mOsm/kgH2O) and low urinary osmolality (92 mOsm/kgH2O) were observed at the admission to our hospital. Plasma arginine vasopressin (AVP) level was inappropriately low (2.2 pg/mL) compared to the high plasma osmolality. Plasma AVP responses to hypertonic-saline infusion were blunted, and her urine osmolality increased in response to desmopressin. The diagnosis of central diabetes insipidus was made from these results. Magnetic resonance imaging (MRI) of hypothalamic-pituitary region demonstrated a significant enlargement of the pituitary stalk, suggesting the presence of hypophysitis. In addition, serum anti-rabphilin-3A antibodies that have been recently reported as a biomarker of lymphocytic infundibulo-neurohypophysitis, were positive. Diabetes insipidus continued after delivery, suggesting that polyuria was not mainly due to excessive vasopressinase activity or reduced renal sensitivity to AVP by prostaglandin E2 that can cause temporal polyuria during pregnancy. We therefore clinically diagnosed central diabetes insipidus due to lymphocytic infundibulo-neurohypophysitis, without performing invasive transsphenoidal pituitary biopsy. This case suggested the usefulness of anti-rabphilin-3A antibodies for the etiological diagnosis of central diabetes insipidus during pregnancy.